Virtual histology uncertainty in synchrotron x-ray micro-computed tomography evaluation. Issue 9 (September 2018) - Lauridsen, T.; Feidenhans'l, R.; Pinholt, E.M.
Abstract: A three-dimensional (3D) X-ray tomogram evaluation gives a full view of the bone distribution around an entire implant in contrast to the often-used two-dimensional (2D) histological methods. High-resolution X-ray absorption tomography was used to evaluate the 3D bone growth around dental implants in an experimental goat mandible reconstruction model. The tomograms allowed for the construction of virtual histological cross-sections that could be used to evaluate the statistical uncertainty of the histological methods, which was the purpose of this paper. The virtual 2D histological results showed a significantly higher uncertainty within the same sample than did the full 3D volume results.